2007
DOI: 10.1007/s10194-007-0373-z
|View full text |Cite
|
Sign up to set email alerts
|

Acute pharmacotherapy of migraine, tension-type headache, and cluster headache

Abstract: In most migraine patients acute therapy is needed. Migraine can be treated either with specific drugs, the triptans and ergot alkaloids, or with NSAIDs. Triptans are a major step foreward in migraine therapy. The therapeutic gain for headache relief is 50% for subcutaneous sumatriptan whereas it is 30-40% for most oral triptans. After oral triptans sustained pain free is only 30%. There is thus still ample room for improvement of acute therapy in migraine. For tension-type headache there is no specific therapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…In fact, migraine treatment can be carried out with triptans and ergot derivatives and NSAIDs. There is no specific therapy for TTH and as a consequence, NSAIDs represent the only treatment [Tfelt-Hansen, 2007]. A communitybased telephone survey [Forward et al, 1998] reported that 98% of TTH sufferers depend on NSAIDs.…”
Section: Nsaids Role In the Acute Treatment Of Headachementioning
confidence: 99%
“…In fact, migraine treatment can be carried out with triptans and ergot derivatives and NSAIDs. There is no specific therapy for TTH and as a consequence, NSAIDs represent the only treatment [Tfelt-Hansen, 2007]. A communitybased telephone survey [Forward et al, 1998] reported that 98% of TTH sufferers depend on NSAIDs.…”
Section: Nsaids Role In the Acute Treatment Of Headachementioning
confidence: 99%
“…In attempts to provide greater efficacy than oral administration and more convenience than SC injection, several other routes of administration for migraine medications have been developed: intranasal (late 1997), orally dissolving tablets (1998), transdermal sumatriptan (2012), bi‐directional intranasal sumatriptan (investigatory), and inhaled dihydroergotamine (investigatory) . Regardless, SC sumatriptan remains the most effective and fastest acting of the available treatment options, with higher reported rates of 2‐hour pain relief and pain freedom than the various other formulations of sumatriptan available (Table ) …”
Section: History Of Needle‐free Sumatriptan Injection In Migraine Thementioning
confidence: 99%
“…Sumatriptan constitutes the archetype of a new class of specific molecules with abortive action, namely triptans, which have now reached their seventh molecule. At present, nonsteriodal anti-inflammatory drugs (NSAIDs) still represent the most common drugs used in acute migraine therapy [5,6].…”
Section: Introductionmentioning
confidence: 99%